亚院二年级学生使用方位词“里”与“中”的偏误分析 MISTAKES OF USING DIRECTIONAL NOUN “LI” AND “ZHONG” IN STBA-PIA STUDENTS SEMESTER IV T.A. 2018/2019 - Dewi Kartika (Journal of Language, Literature and Teaching, 2021)
This study aims to describe the types of errors and the factors that cause errors in the use of directional nouns